PENGUATAN KELOMPOK TANI DESA BANYU ASIN BANGKA MELALUI PENERAPAN TEKNOLOGI TEPAT GUNA DALAM MENINGKATKAN PRODUKTIVITAS DAN NILAI TAMBAH - Yuliyanto, Yuliyanto; Silalahi, Parulian; Muharani, Laily; Kusuma, Rian; Permana Liu, Marcell Candra; Aiwa, Toto (Jurnal Pengabdian Masyarakat Polmanbabel, 2025)
This Community Service Program aims to increase the productivity and competitiveness of the agricultural sector in Banyu Asin Village, Riau Silip District, Bangka Regency. This village, with an area of ??3,354 hectares, has 1,706 hectares of agricultural land, including 106 hectares of rice fields, but faces challenges in the form of the use of traditional technology, limited modern agricultural tools, a suboptimal business management system, and limited marketing access. The main problems faced include three aspects: (1) Production sector - the rice harvesting and drying process is still manual, resulting in low efficiency and the risk of crop loss, especially during the rainy season; (2) Business management sector - lack of understanding of financial management and optimization of BUMDes which is not yet optimal. The program implementation method uses a participatory approach with five stages: socialization, training, technology application, mentoring and evaluation, and program sustainability. The implemented solutions included modernizing production technology through the procurement of modern agricultural equipment, implementing a rice-growing system for income diversification, and optimizing village-owned enterprises (BUMDes).The program's implementation demonstrated significant achievements, including: (1) Transferring appropriate technology through the construction of a rotary drum rice dryer with a capacity of 50-100 kg/batch, which can overcome weather dependence in drying; (2) Developing a rice harvesting aid using a modified grass cutter with a storage container, which increases harvesting efficiency by 5-10 times; (3) Implementing a rice-growing system on a 0.25 hectare plot of land with 1,000 tilapia fish, integrating rice cultivation and fisheries.This program successfully increased farmers' production capacity, reduced crop losses, and diversified income through the rice-growing system. This activity supports the achievement of the Sustainable Development Goals (SDGs), specifically poverty alleviation, food security, and economic growth. It also aligns with the university's Key Performance Indicators (KPI) for student and faculty experiences outside of campus. This community service program is expected to serve as a model for other villages to replicate in implementing appropriate, sustainable agricultural technology, while contributing to improving farmer welfare and regional food security.